1993
DOI: 10.1007/bf00336747
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization, and use in strain improvement of the Cephalosporium acremonium gene cefG encoding acetyl transferase

Abstract: A long open reading frame (ORF) closely linked to the Cephalosporium acremonium gene cefEF was identified by DNA sequencing. The cefEF gene encodes the enzyme involved in cephalosporin C (CPC) biosynthesis known as expandase/hydroxylase. Complementation of a C. acremonium cefG mutant, as well as expression of the gene in Aspergillus niger, showed this ORF to be the cefG gene, encoding cephalosporin C acetyltransferase, which catalyzes the last step in CPC biosynthesis. Analysis of transformants containing addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 15 publications
0
26
0
1
Order By: Relevance
“…Especially genes for ''dispensable'' pathways were shown to be organized in gene clusters, such as genes involved in the synthesis of aflatoxin (Trail et al, 1995), sterigmatocystin (Brown et al, 1996), penicillin (Smith et al, 1990), cephalosporin (Mathison et al, 1993), and trichothecenes (Hohn et al, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…Especially genes for ''dispensable'' pathways were shown to be organized in gene clusters, such as genes involved in the synthesis of aflatoxin (Trail et al, 1995), sterigmatocystin (Brown et al, 1996), penicillin (Smith et al, 1990), cephalosporin (Mathison et al, 1993), and trichothecenes (Hohn et al, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…nidulans (MacCabe et al, 1990), while cephalosporin pathway genes are clustered in Acremonium chrysogenum (syn. Cephalosporium acremonium, Mathison et al, 1993). In P. chrysogenum and A. nidulans the ACV synthetase (pcbAB), IPN synthetase (pcbC), and acyltransferase (penDE) genes are contained within a region of approximately 20 kb in the same order and orientation (Martin and Gutierrez, 1995).…”
Section: Iia Penicillinmentioning
confidence: 99%
“…We cloned the cefG gene from A. chrysogenum CW19 encoding DAC-AT [9] and independently the same gene was also reported by Matsuda et al [10] and Mathison and co-workers [11]. Each of these research groups proposed a different size for the cefG gene based on selection of three different ATG translationinitiation codons in the open reading frame.…”
Section: Figure 1 Reaction Catalysed By the Dac-at Encoded By The Cefmentioning
confidence: 76%
“…This resulted in a protein of 385 amino acids that was assumed to be processed into a leader peptide of 12 amino acids, a subunit of 247 amino acids (27 kDa) and another of 126 amino acids (14 kDa), although they reported that the active form of the enzyme had a molecular mass of 55 kDa. Finally, Mathison and co-workers [11] proposed that the gene would start at the second in-frame ATG codon, resulting in a protein of 399 amino acids (44 kDa), and did not study whether it was processed or not.…”
Section: Figure 1 Reaction Catalysed By the Dac-at Encoded By The Cefmentioning
confidence: 99%